InGaAs-on-Insulator MOSFETs Featuring Scaled Logic Devices and Record RF Performance - Zota, C. B.; Convertino, C.; Deshpande, V.; Merkle, T.; Sousa, M.; Caimi, D.; Czomomaz, L. (2018 IEEE Symposium on VLSI Technology, 2018)
We demonstrate scaled InGaAs-on-insulator FinFETs and planar MOSFETs on Si substrate for low power logic and RF applications. This Si-CMOS compatible technology implements SiN x source-drain spacers and doped extensions for reduced overlap capacitances. FinFETs with performance for logic applications matching state-of-the-art are demonstrated. Simultaneously, f t and f max of 400 and 100 GHz are achieved respectively, the highest reported f t for a III-V MOSFET on Si. Finally, we explore the use of an extended gate line to reduce gate resistance, offering balanced f t /f max of 215/300 GHz, the first report of III-V RF devices on Si matching state of the art Si-CMOS.